2022
DOI: 10.1101/2022.04.07.22273556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-intuitive trends of fetal fraction development related to gestational age and fetal gender, and their practical implications for non-invasive prenatal testing

Abstract: Objective: Discovery of fetal cell-free DNA fragments in maternal blood revolutionized prenatal diagnostics. Although non-invasive prenatal testing (NIPT) is already a matured screening test with high specificity and sensitivity, the accurate estimation of the proportion of fetal fragments, called fetal fraction, is crucial to avoid false-negative results. Methods: We collected 6999 samples from women undergoing NIPT testing with a single male fetus to demonstrate the influence of fetal fraction by the materna… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A 2100 Bionalyzer (Agilent, Waldbronn, Germany) was used for quality control of final libraries. A NextSeq 500/550 platform and High Output Sequencing Kit v2 (75 cycles) (Illumina) with pair-end sequencing protocol (2 × 35 cycles) were used for sequencing [24][25][26].…”
Section: Sample Preparation and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2100 Bionalyzer (Agilent, Waldbronn, Germany) was used for quality control of final libraries. A NextSeq 500/550 platform and High Output Sequencing Kit v2 (75 cycles) (Illumina) with pair-end sequencing protocol (2 × 35 cycles) were used for sequencing [24][25][26].…”
Section: Sample Preparation and Sequencingmentioning
confidence: 99%
“…In our previous study, we demonstrated that the FF of female fetuses was significantly higher than male fetuses at the same gestational age, due to the smaller gonosome Y/chromosome Y and biological differences between the sexes. We also observed that the FF does not grow consistently with fetal maturity due to a drop in 15 weeks of gestation [ 24 ]. The objective of the present study was to analyze the data of 5543 pregnant women who underwent NIPT in the Slovak population including 189 repeated sampling and following analysis due to insufficient FF of the first sampling.…”
Section: Introductionmentioning
confidence: 99%